Stress Factor Influencing the Psoriasis in Tertiary Hospital of Bangladesh (Community Based Medical Journal, 2015)
Psoriasis is one of the major public health problems. It creates a major psychological as well as cosmetic problem and a vast reduction of quality of life in developing countries as well as developed countries as stress is considered to play an important role on the onset and exacerbation of psoriasis. To evaluate influence of stress factor in psoriasis. An observational cross-sectional study was conducted with patients with psoriasis who attended the Department of Dermatology and Venereology, Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period of July 2015 to June 2016. Divorce was presented in 8.1% cases, 51.3% cases had severe life threatening diseases affecting the patient or close family members, 45.1% patients had history of deaths within the close family members, 39.8% patients had serious financial difficulties and 4.4% patients had harassment at school, 65.5% patients experienced first outbreak of psoriasis during a period of stress. About 41.6% psoriatic patients became worse during times of Stress. 38.9% patients had a tendency to break out during times of stress. This study demonstrated that the stress factor is of paramount importance for the development and aggravation of psoriasis.CBMJ 2015 July: Vol. 04 No. 02 P: 49-54